Phacoemulsification with intraocular lens implantation for high myopia cataract - Xiao-Juan Chen (Guoji Yanke Zazhi, 2014)
AIM: To observe the clinical effect of phacoemulsification combined with intraocular lens implantation for high myopia(axis oculi ≥30mm)cataract, and to explore the causes and treatment methods of operation complications. METHODS: Selected 64 cases(86 eyes)of cataract with high myopia patients(axis oculi ≥30mm), vision correction≤0.1. Phacoemulsification combined with intraocular lens implantation was used. During 1a follow-up, the improvement of visual acuity and complications were observed. RESULTS: Postoperative best corrected visual acuity was ≥0.4 in 35 eyes(41%), 0.2-0.3 in 23 eyes(27%), 0.1-0.15 in 25 eyes(29%), <0.1 in 3 eyes(3%). Posterior capsular rupture, vitreous prolapsed occurred in 2 eyes(2%). Through the anterior vitrectomy, intraocular lens was implanted to ciliary sulcus. Postoperative corneal edema in 6 eyes(7%), which was subsided after treatment; Posterior capsular opacity in 9 eyes(10%), visual acuity was recovered after incision of posterior capsule by YAG laser. Retinal detachment in 1 eyes(1%), which was cured after sclera buckling. CONCLUSION: Phacoemulsification combined with intraocular lens implantation is a safe and ideal operation method for high myopia cataract, can obtain good effects, and the postoperative complications can be controlled. Because of the particularity of high myopia, operation should be gentle, technical parameters should be adjusted as appropriate, to achieve the best postoperative effects.